Transformasi Pola Konsumsi Makro Ekonomi di Era Digitalisasi: Analisis Peluang dan Tantangan - Bayu Dian Asmoro Wibowo; Izzati Rohmaniyah; Naily Taufiqoh; Muhammad Taufiq Abadi (CV. ALIM'SPUBLISHING, 2024)
The objectives of this study include: (1) To find out the transformation of macroeconomic consumption in the digitalization era. (2) To find out the opportunities for macroeconomic consumption in the digitalization era. (3) To find out the challenges of macroeconomic consumption in the digitalization era. This type of research uses field research. The method used in this research uses a qualitative approach. Data collection analysis uses interview analysis, literature study, and literature study. The results of interviews with Sharia Economics students of UIN K.H. Abdurrahman Wahid Pekalongan regarding the transformation of macroeconomic consumption in the digitalization era show a significant impact on economic growth, income distribution, and industrial structure. In addition to pointing out the great opportunities in the digital era, such as increased operational efficiency and market access, it also discusses the challenges faced, such as inequality of internet access and the possibility of job loss. Discussions also addressed positive impacts, such as innovation and economic growth, as well as negative impacts, such as the digital divide and income distribution. To ensure a fair and sustainable impact of digitization in the long run, the importance of balanced regulation, consumer protection, and data security was emphasized.